1978
DOI: 10.1104/pp.62.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allopurinol [4-Hydroxypyrazolo(3,4-d)Pyrimidine] on the Metabolism of Allantoin in Soybean Plants

Abstract: Some studies on the effects of xanthble oxiase inhibitor a_opurIo 14-hydroxypyrazolo(34-)pyri.idel on alato met of soybean plants (Glychae max cv. T _ ) are reported.Soyben 'as asepticaly germinated for 96 hours on agar containing I _ilhlmlar allopurinol, contained only slight amounts of aUantoin, allantoic acid, and urea as compared with controls. Analysis of puries and pyrimidines of the allopurinol-treated seedlings sbowed marked accumulation of xanthine both in the cotyedons and seedlin axes. No hypoxanthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 14 publications
3
55
0
1
Order By: Relevance
“…From a preliminary examination it was shown that release of amide nitrogen of asparagine and glutamine during acid extraction could be avoided by using ice-cold 0. (2,5,13), and it has been confirmed that these compounds are mainly produced within nodule tissues via xanthine-uric acid (3,15). From the evidence that atmospheric nitrogen was significantly incorporated into these ureides (4,6), it has been suggested that ureides are the assimilation products of fixed N2 in actively N2-fixing soybean nodules.…”
mentioning
confidence: 95%
“…From a preliminary examination it was shown that release of amide nitrogen of asparagine and glutamine during acid extraction could be avoided by using ice-cold 0. (2,5,13), and it has been confirmed that these compounds are mainly produced within nodule tissues via xanthine-uric acid (3,15). From the evidence that atmospheric nitrogen was significantly incorporated into these ureides (4,6), it has been suggested that ureides are the assimilation products of fixed N2 in actively N2-fixing soybean nodules.…”
mentioning
confidence: 95%
“…Enzymic and inhibitor studies (2,13,26) provided circumstantial evidence that ureide synthesis in these nodules might involve a purine-based pathway (3,10). 02 is required in this pathway for the oxidation of uric acid to allantoin by uricase (EC 1.7.3.3), from either soybean nodules (26) or animal tissue (4,11), which is stimulated by 100% 02 compared to the control treatments in air.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, azaserine is an inhibitor of de novo purine synthesis while allopurinol blocks purine degradation. Fujihara and Yamaguchi (15) found no difference in the amount of ureides in the roots of 3-d-old soybeans after treatment with azaserine. They concluded that de novo synthesis of purines is not involved in ureide production in young seedlings.…”
mentioning
confidence: 99%
“…Plants grown on N-free nutrient solution were harvested as described for azaserine treatment. Four seedlings were placed in flasks containing buffer A with or without 0.5 mm allopurinol (15). The base of the flasks were wrapped in aluminum foil.…”
mentioning
confidence: 99%
See 1 more Smart Citation